Serum 25-hydroxyvitamin D and risk of lung cancer in male smokers: a nested case-control study. - Stephanie J Weinstein; Kai Yu; Ronald L Horst; Dominick Parisi; Jarmo Virtamo; Demetrius Albanes (PLoS ONE)
Background A role for vitamin D in cancer risk reduction has been hypothesized, but few data exist for lung cancer. We investigated the relationship between vitamin D status, using circulating 25-hydroxyvitamin D [25(OH)D], and lung cancer risk in a nested case-control study within the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study of Finnish male smokers. Methods Lung cancer cases (n = 500) were randomly selected based on month of blood collection, and 500 controls were matched to them based on age and blood collection date. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using multivariate-adjusted conditional logistic regression. To account for seasonal variation in 25(OH)D concentrations, season-specific and season-standardized quintiles of 25(OH)D were examined, and models were also stratified on season of blood collection (darker season = November-April and sunnier season = May-October). Pre-determined, clinically-defined cutpoints for 25(OH)D and 25(OH)D as a continuous measure were also examined. Results Overall, 25(OH)D was not associated with lung cancer. Risks were 1.08 (95% CI 0.67-1.75) and 0.83 (95% CI 0.53-1.31) in the highest vs. lowest season-specific and season-standardized quintiles of 25(OH)D, respectively, and 0.91 (95% CI 0.48-1.72) for the ≥75 vs. <25 nmol/L clinical categories. Inverse associations were, however, suggested for subjects with blood collections from November-April, with ORs of 0.77 (95% CI 0.41-1.45, p-trend = 0.05) and 0.65 (95% CI 0.37-1.14, p-trend = 0.07) in the highest vs. lowest season-specific and season-standardized quintiles of 25(OH)D, respectively, and 0.61 (95% CI 0.24-1.52, p-trend = 0.01) for ≥75 vs. <25 nmol/L. We also found 11% lower risk for a 10 nmol/L increase in 25(OH)D in the darker season based on the continuous measure (OR = 0.89, 95% CI 0.81-0.98, p = 0.02). Conclusion In this prospective study of male smokers, circulating 25(OH)D was not associated with lung cancer risk overall, although inverse associations were suggested among those whose blood was drawn during darker months.